Rio de Janeiro’s attempt at Favela urban upgrading - James Miyamoto; Stephen Buckman (Cidades, Comunidades e Território)
Since the end of the 19th century, the city of Rio de Janeiro has witnessed the emergence and growth of informal settlements known as favelas. There have been many attempts to urbanise or even eradicate these settlements. The strategies have not always acted in the best interests of those living in these settlements nor have they met social welfare demands as an objective. Many initiatives have been instituted due to the fact that most favelas occupy central regions and are in a permanent state of tension with the so-called asfalto or asphalt city, also known as the formal city. Among these public initiatives was the Favela-Bairro programme which began in 1994 intending to urbanise 15 medium-sized favelas. The success of the infrastructure-driven programme has led to its expansion and the creation of other similar programmes — Bairrinho, for favelas with fewer than 500 houses, and Grandes Favelas, for communities with more than 2,500 residences. This study examines the growth of these programmes three decades after their initial development. Conclusions from this study show that even though the Favela-Bairro programme was paved with good intentions, it has done little to alleviate persistent poverty-driven issues that residents of Rio’s favelas face.